Identifying professional functionings of early childhood educators. Issue 4 (8th August 2019) - Molla, Tebeje; Nolan, Andrea
Abstract: What does being a professional early childhood educator entail? This paper aims to address this question. Starting from the early 2000s, there has been increased attention to workforce professionalization in the early childhood education and care sector across OECD nations. Against the backdrop of recent early childhood workforce professionalization initiatives in Australia, and drawing on the Capability Approach to human development as an analytical framework, in this paper, we identify five evaluative spaces for assessing professional functionings: expertise, deliberation, recognition, responsiveness and integrity. We also argue that understanding what educators are actually able to be and do in their professional practices vis-à-vis policy expectations is instrumental in (a) identifying areas of professional learning needs, and (b) devising transformative learning experiences.